Adrenergic Signaling-Induced Ultrastructural Strengthening of Intercalated Discs via Plakoglobin Is Crucial for Positive Adhesiotropy in Murine Cardiomyocytes - Yeruva, Sunil; Kempf, Ellen; Egu, Desalegn Tadesse; Flaswinkel, Heinrich; Kugelmann, Daniela; Waschke, Jens (Frontiers in Physiology, 2020)
Intercalated discs (ICD), which connect adjacent cardiomyocytes, are composed of desmosomes, adherens junctions (AJ) and gap junctions (GJ). Previous data demonstrated that adrenergic signaling enhances cardiac myocyte cohesion, referred to as positive adhesiotropy, via PKA-mediated phosphorylation of plakoglobin (PG). However, it was unclear whether positive adhesiotropy caused ultrastructural modifications of ICDs. Therefore, we further investigated the role of PG in adrenergic signaling-mediated ultrastructural changes in the ICD of cardiomyocytes. Quantitative transmission electron microscopy analysis of ICD demonstrated that cAMP elevation caused significant elongation of area composita and thickening of the ICD plaque, paralleled by enhanced cardiomyocyte cohesion, in WT but not PG-deficient cardiomyocytes. STED microscopy analysis supported that cAMP elevation ex vivo enhanced desmoglein-2 (Dsg2) and N-cadherin (N-cad) staining in ICDs of WT but not PG-deficient cardiomyocytes. For dynamic analyses, we utilized HL-1 cardiomyocytes, in which cAMP elevation induced translocation of Dsg2 and PG but not of N-cad to cell junctions. Nevertheless, depletion of N-cad but not of Dsg2 resulted in a decrease in basal cell cohesion whereas positive adhesiotropy was abrogated in monolayers depleted for either Dsg2 or N-cad. Similarly, AFM experiments showed that the cAMP elevation-induced increase in Dsg2 binding events close to cell junctions was abolished by depletion of either Dsg2 or N-cad. Our data demonstrate that in murine hearts adrenergic signaling enhanced N-cad and Dsg2 in the ICD paralleled by ultrastrutural strengthening of ICDs and that effects induced by positive adhesiotropy were strictly dependent on Pg.